The Historian Dionysius of Halicarnassus and the Gods - Parker, Robert (Histos, 2023)
This article looks in detail at Dionysius’ presentation of the role of what he calls ‘the daimonion’ in human affairs; he sees it often at work, usually in support of justice and thus, in the main, of Rome; he regularly sees providence guiding Roman fortunes, but also deplores contemporary neglect for the guidance provided by divination. It notes the traditional stories that he rejects as ‘myth-like’ (μυθώδη), but also the many about which he is less sceptical than his near contemporary Livy. Like another near contemporary Diodorus Siculus, Dionysius represents a bounce back from hard-headed Polybian scepticism; but he is reluctant to accept myths that offend against an exalted conception of the divine nature.